Genetic Factors Causing the Prevalence of Anemia in Young Girls and Stunting in Toddlers: A Systematic Literature Review - Afrina Mizawati; Nursyirwan Effendi; Delmi Sulastri; Rozi Sastra Purna (Jurnal Penelitian Pendidikan IPA, 2023)
The prevalence of anemia in adolescents at the national level is still considered quite high. Several factors are associated with the incidence of anemia in female adolescents, namely energy intake, protein intake, iron intake, vitamin C intake, tea or coffee drinking habits, investment in worms, knowledge, education and type of parental occupation, family income, and menstrual patterns as well as genetics. Stunting is also still a problem in Indonesia due to insufficient nutritional intake for quite a long time. Stunting occurs when the fetus is still in the womb and only appears when the child is two years old. anemia caused by malnutrition at an early age increases infant and child mortality. anemia in young women and also stunting in children is very dangerous. Where the purpose of research is to explain Genetic Factors Causing the Prevalence of Anemia in Young Girls and Stunting in Toddlers. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. We review literature from several publications and analyze genetic factors that cause the prevalence of anemia in young women. The prevalence of anemia among young women is also caused by genetic factors. Young women tend to experience anemia because during this period they experience growth and development. The risk of anemia increases with physiological shifts such as menstrual periods. To prevent anemia, the government has planned a program for the Prevention and Control of Iron Nutrition Anemia in women of childbearing age which aims to reduce the prevalence of iron deficiency anemia in high school and junior high school students.